EFSA Guidance Document for evaluating laboratory and field dissipation studies to obtain DegT50 values of active substances of plant protection products and transformation products of these active substances in soil. (8th May 2014) - ,
Abstract: EFSA was asked by the European Commission to prepare a Guidance of EFSA for evaluating laboratory and field dissipation studies to obtain degradation rate parameters (DegT50matrix values) of active substances of plant protection products and transformation products of these active substances in soil. This EFSA Guidance Document provides guidance for users on how to obtain DegT50matrix values when performing risk assessments according to Regulation EC No 1107/2009 of the European Parliament and the Council. In addition, this document provides guidance on adsorption parameter (Koc) selection and new Crop Interception values.